2021
DOI: 10.3390/app11198813
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Physical Education Classes on Health and Quality of Life during the COVID-19

Abstract: The purpose of this study was to examine the effects of the COVID-19 pandemic on the well-being and the quality of life of college students participating in physical education classes. We consider this study to be relevant because during the COVID-19 pandemic we tested whether the boost in effective activity among physical education class participants affected well-being and quality of life. A sectional questionnaire survey was conducted across Taiwan in 2019–2020. Data were collected in two stages within 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Nowadays, most of the world are facing a high risk pandemic that has a huge negative impact on all areas including physical education in elementary schools to universities (López-Valenciano, Suárez-Iglesias, Sanchez-Lastra & Ayán, 2021;Roe, Blikstad-Balas & Dalland, 2021;Fang, Teng & Wang, 2021). Data reported that the COVID-19 pandemic caused athletes and teachers to carry out offline teaching while some people claimed that online teaching had various obstacles and did not provide optimal results (Jumareng et al, 2021;Sortwell & Ramirez-Campillo, 2022), which could led to a significant decrease in their talent related to physical literacy (Duclos-Bastías, Vallejo-Reyes, Giakoni-Ramírez & Parra-Camacho 2021; Young, O'Connor, Alfrey & Penney, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, most of the world are facing a high risk pandemic that has a huge negative impact on all areas including physical education in elementary schools to universities (López-Valenciano, Suárez-Iglesias, Sanchez-Lastra & Ayán, 2021;Roe, Blikstad-Balas & Dalland, 2021;Fang, Teng & Wang, 2021). Data reported that the COVID-19 pandemic caused athletes and teachers to carry out offline teaching while some people claimed that online teaching had various obstacles and did not provide optimal results (Jumareng et al, 2021;Sortwell & Ramirez-Campillo, 2022), which could led to a significant decrease in their talent related to physical literacy (Duclos-Bastías, Vallejo-Reyes, Giakoni-Ramírez & Parra-Camacho 2021; Young, O'Connor, Alfrey & Penney, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The physical education programmes in several countries have experienced significant transformations due to the global impact of the COVID-19 pandemic (Fang, Teng & Wang, 2021;López-Valenciano, Suárez-Iglesias, Sanchez-Lastra & Ayán, 2021;Mendes, Fachada, Melo, Campos, Nobre & Machado-Rodrigues, 2023;Mujriah et al, 2022). Prior to the onset of the COVID-19 pandemic, the predominant mode of instruction within the university setting involved in-person interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In point of fact, physical education is on par with the significance of other academic subjects because of the crucial part it plays in the development and health of students as a whole [7]. To maintain the culture within the campus would result in excellent physical fitness (such as perfection in motor skills and abilities), the positive growth of vital forces, and the moral, aesthetic, and intellectual development of the students [8][9][10].…”
Section: Introduction Physical Culture On Campusmentioning
confidence: 99%